Strategies to improve outcomes in esophageal adenocarcinoma. Issue 6 (June 2014) - Cowie, Andrew; Noble, Fergus; Underwood, Timothy
<x xml:space="preserve">Abstract</x> Esophageal adenocarcinoma is one of the fastest rising cancers in Western society. Incidence has increased by 600% within the last 30 years. Rates of diagnosis and death run parallel due to the poor prognosis and a lack of effective treatments. Potentially curative treatments are followed by high rates of disease recurrence. For the majority of patients, who present with advanced disease, we have no effective treatment. We discuss the key areas of progress in this demanding field and offer our views on the direction of future research and treatment.